Answer:
I think this is a pretty good question of law of indices
Explanation:
Given that
![(9^p)(27^q)=3^n\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/3hvjuo5uc8yh0n13fqzfu0xaf9g5xfehd5.png)
a) express n in terms of p and q ,
b) hence if p = 1 and q = 2 find the value of n
Solution to part a)
![(9^p)(27^q)=3^n\\\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/qo74h8d5pz3ah3t2vrjxfa61t75zi9p6yr.png)
Simplify the equation and how do we do that? As we can see that 9 can also be written as 3^2 and 27 can be written as 3^3 we can rewrite the following equation like this,
![(3^2)^p(3^3)^q=3^n\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/8f3532fcxhjqoln4uoc4kmtih0djtpymvf.png)
now we multiply p with 2 and
multiply q with 3 respectively,
![(3^(2p))(3^(3q))=3^n\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/acsz64juwx08akjs1ocjotb6001spbcgvk.png)
now since the bases are same and are multiplying the exponents will add themselves like this, in this equation the number 3 is the base
![3^(2p+3q)=3^n\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/xdwlb2z2hk6mr9wz5mojsn8s9ck84iohz2.png)
now since the bases on the left hand side and on the right hand side are equal the exponents will also be equal so now,
![2p+3q=n\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/kvlxv1q06zykrzq7xvtyx4y5fu27rui63t.png)
hence n is expressed in terms of p and q
Solution to part b)
if p = 1 and q = 2 we plug in these values in the above equation we found for n
n = 2p + 3q
n = 2(1) + 3(2)
n = 2 + 6
n = 7